Resource Use Efficiency of Wheat Seed Production: A Case from Chitwan, Nepal - Narayan Prasad Tiwari; Suryamani Dhungana (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2023)
Wheat is staple food for more than thirty percent of the world population and is also a rich source of minerals, proteins, vitamins and dietary fibers. Quality seed is the major reason behind the low productivity of wheat in Nepal. The study was design to investigate the cost, return, and resource use efficiency of wheat seed production in Chitwan district of Nepal. The study used 160 randomly sampled sample of wheat seed producer. Cobb-Douglas production function and benefit cost ratio were used to estimate the resource use efficiency during wheat seed production through data collected using semi-structured interview schedule to meet the objective. The average total cost of wheat seed production with subsidy was NRs. 59440 per hectare and average total cost of wheat seed production without subsidy was NRs. 60731 per hectare. The yield in study area was found 2771.02 kg. The return, profit with subsidy and profit without subsidy from wheat seed production was NRs. 69275.49, NRs. 9835.04 and NRs. 8544.46 in the study area respectively. The benefit cost ratio of wheat seed production in the study area with subsidy was found 1.31 and 1.28 without subsidy. The wheat seed production was found increasing return to scale (RTS = 1.106) in the study area. Seed and Machine were underutilized and other inputs like Farmyard Manure (FYM), chemical fertilizer, labor and other cost were over utilized while producing wheat seed in Chitwan district. The study revealed we can increase profit by optimization of input uses.